Hubungan Stres Terhadap Tekanan Darah pada Lansia Hipertensi di Wilayah Kerja Puskesmas Kadungora Kabupaten Garut - Citra Windani Mambang Sari; Nina Sumarni; Yuliana Sri Rahayu (Jurnal Keperawatan Muhammadiyah, 2019)
Hypertension will often occur in the elderly due to physiological decline and stress will trigger an increase in blood pressure if it lasts a long time it will cause persistent high blood pressure This research aims to know the correlation between stress and blood pressure in elderly with hypertension at the working area of Community Health Center of Kadungora, Garut RegencyThis was a correlational descriptive research which used cross sectional approach and total sampling technique with 116 elderlies who suffer from hypertension.The instrument of the research was DASS (Depression, Anxiety, and Stress Scale) which consisted of 14 questions and used digital sphygmomanometer to measure the blood pressure. The results of this study were obtained the normal category stress  32 respondens (27,6%), mild stress 45 respondents (38.8%), moderate stress 29 respondents (25.0%) and severe stress 10 respondents (8.6 %). The results of blood pressure 130-139 mmHg / 80-89 mmHg were 30 respondents (25.9%), ≥140 mmHg / ≥90 mmHgs 79 respondents (68.1%) and ≥180 mmHg / ≥120 mmHg as many as 7 respondents ( 6.0%). From the analysis result, the significant value of p=0,024 which means that it significant effect and thus the H1 can be accepted that there is a significant correlation between stress and blood pressure on hypertension elderly in the working area of Community Health Center of Kadungora, Garut Regency. Medical staffs are expected to use this research as the basic in developing health care activities for elderlies such as Integrated Development Post (posbindu) by providing socialization about information and education related with stress and blood pressure.